Menulis Di Jurnal Hukum: Gagasan, Struktur, Dan Gaya - Wibisana, Andri Gunawan (Jurnal Hukum & Pembangunan, 2019)
Writing articles in a law review is different from writing an opinion in a newspaper or articles in other types of journals. Indonesian authors often fail to indicate the problems to be discussed, the proposed thesis statement or idea (claim), and the structure of the article. They also write too descriptive and employ very limited references. This paper aims to support the authors to find out important aspects in formulating a good legal article. For this reason, this paper explains that an article must contain the claim, and be novel, non-obvious, and useful. This paper also explains the importance of the introduction of an article and explains how to start the introduction. The article demonstrates the importance of the structure of articles, references, and languages. By knowing and taking into account the elements of good articles, Indonesian authors would be able to produce articles with quality comparable to that of reputable international journals. In this case, the only problem for a publication in reputable international law journals would only be a matter of writing an article in English and no longer of the quality of the article.